QUALITY IMPROVEMENT OF VIRGIN COCONUT OIL (VCO) BY FERMENTED DRY CULTURE OF LACTIC ACID BACTERIA (BAL) TO YIELD AND WATER CONTENT - Arisanti, Desi; Angelia, Ika Okhtora (Universitas Djuanda, 2020)
Virgin Coconut Oil contains medium chain fatty acids that are easily digested and oxidized by the body so as to prevent accumulation in the body. This research will try to produce virgin coconut oil / VCO by fermentation and using various variations of the concentration of BAL dry culture starter. The use of BAL dry culture has several advantages including being able to be stored for a long time in cold temperatures, easily applied and cost efficiency. The purpose of this study was to determine the percentage of Free Fatty Acid (FFA) and yield produced in the fermentation process of virgin coconut oil. Because the lower the FFA value produced the higher the quality of the oil produced The parameters observed in this study are the percentage of Free Fatty Acid (FFA), yield of virgin coconut oil (VCO), and water content. This study used a complete randomized design with 1 factor, namely the concentration of BAL dry culture, with the following research treatments: A1 = 5 gram of BAL dry culture; A2 = 10 gram of BAL dry culture; A3 = 15 gram of BAL dry culture; A4 = 20 gram of BAL dry culture. From the results of the study it can be concluded that the best treatment of water content is in treatment A3 which is 0.1463%. The best treatment yield was in treatment A1, which was 13.336%.